Evaluation of the Nutritional Value of Rice Crackers Made from Local Raw Rice and Rinuak Fish (Psilopsis sp) - Wellyalina, Wellyalina; Aisman, Aisman; Rahmadila, Anindya (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Rice crackers are snacks made from rice flour that have a crunchy texture, salty and savoury taste. Making rice crackers with local raw materials of brown rice and rinuak fish is expected to increase the quality of the food so that it can be a complementary food product, expected to be able to add to the quality of the food so that it can be a functional complementary food product, functional complementary food product. This study aims to determine the chemical properties and nutritional value of rice crackers made from red rice and rinuak fish. red rice and rinuak fish. This research was conducted using an exploratory method through laboratory experiments laboratory. The treatments used were the ratio of brown rice and rinuak fish and legumes. This treatment was carried out with 3 replications so that the results can be said to be valid. The results showed that each brown rice crackers with the addition of rinuak fish and nuts have the advantage of their respective nutritional content on the rice crackers obtained. The making of brown rice crackers with the addition of rinuak fish and nuts can increase the content of nutritional value, physiological effects on the body, and diversification of complementary food products. Contribution to Sustainable Development Goals (SDGs):SDG 3: Zero HungerSDG 3: Good Health and Well-BeingSDG 8: Decent Work and Economic GrowthSDG 12: Responsible Consumption and ProductionSDG 15: Life on Land